Exploring the Concept of Autonomous Learner in Language Teaching - Iman Ali Ahmed Al-Rashed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Autonomy is a philosophical concept which deeply means shaping the character of a person. In education, it is related to the teaching approaches and methods. Autonomous learner is able to be responsible for his own learning. The paper directs attention to the importance of building autonomous learner. It employs a quantitative and a qualitative method to collect data in the form of a questionnaire, observations and interviews. The autonomy conception of the instructors and students is investigated and evaluated. The results reveal that there is a need to improve the beliefs of college instructors and students.